Using synthetic biology to improve photosynthesis for sustainable food production - da Fonseca-Pereira, Paula; Siqueira, João Antonio; Monteiro-Batista, Rita de Cássia; Vaz, Marcelo Gomes Marçal Vieira; Nunes-Nesi, Adriano; Araújo, Wagner L. (Journal of biotechnology, 2022)
Photosynthesis is responsible for the primary productivity and maintenance of life on Earth, boosting biological activity and contributing to the maintenance of the environment. In the past, traditional crop improvement was considered sufficient to meet food demands, but the growing demand for food coupled with climate change has modified this scenario over the past decades. However, advances in this area have not focused on photosynthesis per se but rather on fixed carbon partitioning. In short, other approaches must be used to meet an increasing agricultural demand. Thus, several paths may be followed, from modifications in leaf shape and canopy architecture, improving metabolic pathways related to CO2 fixation, the inclusion of metabolic mechanisms from other species, and improvements in energy uptake by plants. Given the recognized importance of photosynthesis, as the basis of the primary productivity on Earth, we here present an overview of the latest advances in attempts to improve plant photosynthetic performance. We focused on points considered key to the enhancement of photosynthesis, including leaf shape development, RuBisCO reengineering, Calvin-Benson cycle optimization, light use efficiency, the introduction of the C4 cycle in C3 plants and the inclusion of other CO2 concentrating mechanisms (CCMs). We further provide compelling evidence that there is still room for further improvements. Finally, we conclude this review by presenting future perspectives and possible new directions on this subject. •Sunlight is cost-free and a widely abundant energy source on Earth.•Key photosynthetic aspects must be optimized in addressing our agricultural needs.•Artificial photosynthesis is an attractive replacement for fossil fuels.•Redirecting photosynthesis for the synthesis of target bioproducts is discussed.•Efforts to enhance the nutritional value of plants have attracted great attention.